PERAN PENDIDIK SEBAGAI AGENT OF CHANGE DALAM PENDIDIKAN ORANG DEWASA - Syafuddin, Khairul (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study examines the role of educators as agents of change, particularly in the context of adult education. Through a comprehensive literature review, this study explores the theoretical underpinnings and practical implementation of educators as catalysts for societal transformation. The findings of this study highlight that educators have a critical role in shaping individuals and societies. As agents of change, they not only impart knowledge but also foster critical thinking, skills, and a lifelong love of learning. This study underscores the importance of educators’ professional development, with emphasis on the need for ongoing training and support, particularly to equip them with the competencies needed to navigate the complexities of modern education. This study also examines the challenges educators face in fulfilling their role as agents of change, including limited resources, varying levels of learner engagement, and rapid technological advances. To address these challenges, strategies such as fostering collaborative partnerships, leveraging technology, and promoting learner-centered approaches are needed.